Earthquake induced floor horizontal accelerations in buildings. - Rodriguez, M.E.
Floor horizontal accelerations are needed for obtaining forces for the design of diaphragms, for the design of their connections and for the design of non structural components and equipment supported by structures. Large floor horizontal accelerations have been recorded in buildings during earthquakes. Such accelerations have been responsible for inertia forces causing damage to services and are a major reason for structural damage and even building collapse. This paper describes an analytical investigation into earthquake induced floor horizontal accelerations that arise in regular buildings built with rigid diaphragms. The paper also describes several methods prescribed by design standards and proposes a new method. The method is based on modal superposition modified to account for the inelastic response of the building's lateral force resisting system. Results obtained from time history inelastic analysis are compared with the proposed method.
Keywords: Floor accelerations; Diaphragms; Non structural components; Non linear analysis; Seismic demands; Building codes